Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/admi.202201924
|View full text |Cite
|
Sign up to set email alerts
|

High‐Quality Femtosecond Laser Surface Micro/Nano‐Structuring Assisted by A Thin Frost Layer

Abstract: Femtosecond laser ablation has been demonstrated to be a versatile tool to produce micro/nanoscale features with high precision and accuracy. However, the use of high laser fluence to increase the ablation efficiency usually results in unwanted effects, such as redeposition of debris, formation of recast layer, and heat‐affected zone in or around the ablation craters. Here this limitation is circumvented by exploiting a thin frost layer with a thickness of tens of microns, which can be directly formed by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…As ripple generation has been suppressed, this result might be considered experimental evidence that the temperature field is the positive feedback mechanism needed for structure formation, as described in [22,28,64]. Interestingly, cooling of the target silicon surface in [61] had the contrary effect and gave rise to high-spatial-frequency LIPSS. In the future, interesting follow-up experiments would include high-speed camera recording of bubble generation during laser processing, water temperature measurements, physicochemical analysis of the liquid after laser irradiation, and nanostructure analysis upon substrate cooling at various temperatures.…”
Section: Nanoripplesmentioning
confidence: 74%
See 1 more Smart Citation
“…As ripple generation has been suppressed, this result might be considered experimental evidence that the temperature field is the positive feedback mechanism needed for structure formation, as described in [22,28,64]. Interestingly, cooling of the target silicon surface in [61] had the contrary effect and gave rise to high-spatial-frequency LIPSS. In the future, interesting follow-up experiments would include high-speed camera recording of bubble generation during laser processing, water temperature measurements, physicochemical analysis of the liquid after laser irradiation, and nanostructure analysis upon substrate cooling at various temperatures.…”
Section: Nanoripplesmentioning
confidence: 74%
“…Similarly, the spatial periods diminished by several times, when LIPSS on metals were produced by a femtosecond laser in liquid environments instead of air [60]. Interestingly, a water film that was generated by melting a thin frost layer on the target silicon surface not only increased the quality of laser-ablated microstructures considerably but also gave rise to high-spatial-frequency LIPSS [61]. These were not generated at all without the frost layer, even when the same processing parameters had been applied.…”
Section: Nanoripplesmentioning
confidence: 99%
“…LIPSS includes low-spatial-frequency LIPSS (LSFL) for the wavelength order and high-spatial-frequency LIPSS (HSFL) for the subwavelength order [ 44 , 45 ]. In femtosecond laser machining, HSFL processing has a strong capability to produce high-efficiency and large-area uniform hierarchical nanotextures [ 46 ]. Typically, the direction of the LSFL texture is perpendicular to the polarization direction of the incident laser, whereas the direction the HSFL texture is parallel to the polarization direction of the incident laser [ 47 ].…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…An interesting and original effect of the influence of temperature regime on LST processing and LIPSS formation was presented in the newest work by W. Gao et al [ 123 ]. In this work, it was shown that decreasing the laser-processed surface temperature to below the freezing point has the potential to dramatically change the LST process.…”
Section: Physical Limitations Of Laser Surface Texturingmentioning
confidence: 99%